KUALITAS PASAR OBLIGASI KORPORASI INDONESIA - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2011)
lndonesia corporate bond market development can he done from various aspects, among others, through the stability and improvement of macroeconomic indicators, improving the quality of ï¬nancial infrastructure, and improving the quality of the corporate bond market. This study aimed to describe the quality Indonesian corporate bond market based transaction costs approach. Therefore, the quality of the corporate bond market in this study manifested by transaction costs and decomposition of transaction costs (information friction and real friction). Based on the estimation of transaction costs and decomposition of transaction costs, regulators and market managers can create a variety of policies to improve the quality of the corporate bond market. To achieve these goals, the data used were corporate bond registered and transacted in the bond market and the sources of data from Securities Division reported OTC-FIS (Over the counter â€“ Fixed Income Service). The research samples were 2336 observations using the purposive sampling technique to gather samples. The data were analyzed using the multiple regression equation. The research indicates that: First, transaction costs tyâ€™ corporate bond is 0-798 with t-statistic is 31.964. Second, the contribution of information friction againts transaction cost is 45.1 percent with t-statistic is 18.20. "third, the contriliution real friction againts transaction cost is 14.2 percent with t-statistic is 5.71. Fourth, the information friction have the greater contribution to transaction cost with or without the classification of sample. Fifth, in the change of bond price segmentation, the contribution of information friction increases with the increase of the change of bond price. With reference to the research results, the quality of the corporate bond market can he improved by lowering the transaction costs in trade mechanism. Transaction costs can be reduced through increased transparency and improved the trading niechanisni of corporate bond market. Furthermore, the result if this research can be used by investors in creating portfolios and holding periods and for bond emitters in issuing bonds.